Analisis Kesadaran Mahasiswa dalam Meminimalisir Dampak Lingkungan Akibat Sampah: Studi Kasus pada Penyelenggaraan FestVent 2025 - Katherine Celestiana Tjhai; Delice Arnelita Susanto; Stephanus Garland Jordan Oeswadi; Aditya Rizki Rinaldi (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2026)
Environmental degradation resulting from the special event and MICE (Meetings, Incentives, Conventions, and Exhibitions) sectors necessitates minimization through the awareness and tangible contributions of all involved parties. The primary objective of this study is to analyze the level of awareness among 2023 batch student committee members of Multimedia Nusantara Polytechnic (MNP) regarding environmentally friendly practices, specifically in minimizing the environmental impact of waste generated during the 2025 FestVent event. This research employs a qualitative descriptive and observational methodology, collecting data through in-depth interviews complemented by direct observation conducted from September 18 to 20, 2025. A total of 19 informants were utilized, comprising committee coordinators, volunteers, and event attendees. The interview findings will be analyzed to identify student perspectives concerning eco-friendly practices implemented during the 2025 FestVent. The results of this study will serve as key indicators of the organizing students' awareness and contribution towards realizing sustainable event management.